2014
DOI: 10.1177/1757177414551562
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial effect of 2-octyl cyanoacrylate (Dermabond®) skin adhesive

Abstract: Dermabond® is a tissue adhesive commonly used for wound or surgical incision closure. Its use has previously been associated with a reduction in wound infection, and it has been thought to act as a physical barrier to bacteria accessing the wound. This study aimed to establish whether the Dermabond® adhesive demonstrated any intrinsic antimicrobial properties. Solidified pellets of Dermabond® were placed on standardised Agar plates cultured with a variety of pathogens. Inhibition of growth was demonstrated aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…In fact, cyanoacrylate adhesives have been considered by several schools with antibacterial properties, but were attributed initially to the formation of a film that protect the cells, and in this sense as a barrier for the access of bacteria to the wound . However, Rushbrook et al have demonstrated recently that this is not the exclusive reason and in a deep analysis of the antibacterial effect of 2‐octyl cyanoacrylate skin adhesive (Dermabond) they have found a clear intrinsic bactericidal effect against Gram‐positive bacteria. Therefore, we can consider that the application of cyanoacrylic adhesives provides a considerable antibacterial effect independently of the nature of the corresponding compound.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, cyanoacrylate adhesives have been considered by several schools with antibacterial properties, but were attributed initially to the formation of a film that protect the cells, and in this sense as a barrier for the access of bacteria to the wound . However, Rushbrook et al have demonstrated recently that this is not the exclusive reason and in a deep analysis of the antibacterial effect of 2‐octyl cyanoacrylate skin adhesive (Dermabond) they have found a clear intrinsic bactericidal effect against Gram‐positive bacteria. Therefore, we can consider that the application of cyanoacrylic adhesives provides a considerable antibacterial effect independently of the nature of the corresponding compound.…”
Section: Resultsmentioning
confidence: 99%
“…At least one study has shown 2‐octyl cyanoacrylate skin adhesive to have antimicrobial properties against gram‐positive bacteria, and multiple studies have shown lower rates of surgical site infection with superficial cyanoacrylate closures than with traditional closure techniques such as staples and sutures . Cyanoacrylate tissue adhesives should not be used in tension‐bearing wounds, hairy areas, crush wounds, areas of high moisture, or wounds at high risk of infection .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of reported complications associated with their use such as embolism and needle impaction [10], cyanoacrylate has been reported to have higher hemostasis and lower rebleeding rates than traditional band ligation and sclerotherapy in gastroesophageal varices [2]. Moreover, they have been reported to have antibiotic activity towards gram-positive bacteria [11].…”
Section: Introductionmentioning
confidence: 99%